1996
DOI: 10.1097/00004032-199601000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Development of a System to Evaluate and Communicate Radiation Risk

Abstract: Review of research protocols involving positron emission tomography studies on healthy volunteers focused attention on the radiation exposure disclosure statements contained in the informed consent form. Of particular concern was the observation that breast doses from positron emission tomography studies are greater than breast doses from other research uses of radioisotopes, as well as routine nuclear medicine and radiographic procedures. Disclosure of individual organ doses is not normally provided on inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some have suggested that it may be appropriate to provide the individual organ doses, although this is not normally included in informed consent forms. 24 One study of institutional review boards' (IRBs') acceptance of risk statements for studies that involve exposure to radiation concluded that risk statements were more likely to compare study risks with those in a similar radioactive study or with the Radioactive Drug Research Committee (RDRC) organ radiation limits. A smaller number of IRBs compared exposure with Nuclear Regulatory Commission (NRC) occupational or nonoccupational limits.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested that it may be appropriate to provide the individual organ doses, although this is not normally included in informed consent forms. 24 One study of institutional review boards' (IRBs') acceptance of risk statements for studies that involve exposure to radiation concluded that risk statements were more likely to compare study risks with those in a similar radioactive study or with the Radioactive Drug Research Committee (RDRC) organ radiation limits. A smaller number of IRBs compared exposure with Nuclear Regulatory Commission (NRC) occupational or nonoccupational limits.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have published examples of radiation risk statements that could be used to inform the consent of participants (including healthy volunteers) in medical research [2,8,[13][14][15]. The information provided to participants who are also patients should state that they will be exposed to ionising radiation and the procedures should be named.…”
Section: The Information That Should Be Providedmentioning
confidence: 99%